The Influence of Health Education on CleaningAtopic Dermatitis Wounds With Normal Saline Solution Against Students' Knowledge At The St. Fransiskus Assisi Boys' Dormitory, Kabanjahe - Herianto Bangun; Dameria Br Ginting (International Journal of Health and Pharmaceutical (IJHP), 2026)
Atopic dermatitis, also known as eczema, is a chronic inflammatory condition of the skin that often results in red, itchy, and inflamed patches on the skin. These patches can become open sores or sores that require proper care and treatment. Cleaning to speed healing and prevent infection. This type of research is Quasi-experimental research using a Pre-Experiment Design with a One group Pre test – Post test design. The results showed that of the 60 students who had a good level of knowledge at the pre-test, there were 7 people (11.7%), the level of knowledge was sufficient for the students at the pre-test, there were 24 people (40%) and the level of knowledge was poor for the students. during the pre-test there were 29 people (48.3%). The research results showed that of the 60 students who had a good level of knowledge at the post-test, 12 people (20%), had a sufficient level of knowledge at the post-test, 48 people (80%). The statistical test results showed that p-value = 0.000, p-value <0.05, meaning that there was a significant increase in knowledge scores between before and after providing education.